1997
DOI: 10.1002/masy.19971140120
|View full text |Cite
|
Sign up to set email alerts
|

Study of metal clusters intercalation into cellulose by waxs, spectroscopic, and microscopic methods

Abstract: Cellulose substrates are increasingly used as supports and fillers in medicine, as membranes and components of organic sensors. In the present paper the WAXS as well as SEM, TEM, XRF, EDXA, ESCA, FTIR, Raman, and I3C NMR were used to study methods of metal clusters intercalation (taking as an example silver clusters) into the cellulose matrix and changes of cellulose structure in the resulting samples in bulk after this intercalation. Clusters in matrix can be formed simultaneously with the appearance of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This indicates that the nanoparticles are anchored on the surface or in the amorphous parts of the microfibrils. The same phenomenon was observed already in previous studies on cellulose noble metal nanocomposites [2,[7][8][9]. Scattering from the nanoparticles revealed that the diffraction maxima of the CuO crystallites (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This indicates that the nanoparticles are anchored on the surface or in the amorphous parts of the microfibrils. The same phenomenon was observed already in previous studies on cellulose noble metal nanocomposites [2,[7][8][9]. Scattering from the nanoparticles revealed that the diffraction maxima of the CuO crystallites (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The porous cellulose matrix has been described as a nanoreactor for metal nanoparticles [7,8] and it has been shown to be a useful support material for platinum, palladium, silver, and nickel nanoparticles [2,7,[9][10][11]. Bacterial cellulose supported Pd was found to be capable of catalysing the generation of hydrogen and to be a suitable polyelectrolyte membrane for fuel cells [10].…”
Section: Introductionmentioning
confidence: 99%